Predictors of overall survival after surgery in gastric cancer patients from a Latin-American country - Cordero-García, Eugenia (J Gastrointest Oncol, 2018)
BACKGROUND: Gastric cancer is one of the major causes of cancer-related deaths in several Latin-American countries, including Costa Rica. However, determinants of poor outcomes are fairly unknown for patients from this region. The aim of this study was to determine prognostic variables of overall survival (OS) in a cohort of Hispanic patients after curative-intent surgery for gastric cancer. METHODS: We retrospectively evaluated the clinical records of 236 consecutive patients who underwent surgery for advanced gastric cancer at four major hospitals in Costa Rica. Univariate and multivariate Cox proportional models were used to assess the influence of age, sex, clinical stage, adjuvant therapy, type of dissection (D1 vs. D2), extent of gastrectomy (partial vs. total), margin status (R0 vs. R1/2), tumour differentiation, and tumour location on OS. RESULTS: After a median follow-up of 46.5 months, median OS was 47.6 months [95% confidence interval (CI): 34.7–60.4]. There was no survival benefit of adjuvant chemotherapy [hazard ratio (HR): 1.18; 95% CI: 0.70–2.00; P=0.53] or postoperative chemoradiotherapy (CRT) (HR: 1.04; 95% CI: 0.71–1.52; P=0.85) compared to surgery alone. After adjustment for potential confounders, the R0 status was associated with better OS (HR: 0.51; 95% CI: 0.28–0.92; P=0.03). Similarly, clinical stage (III vs. I) (HR: 2.26; 95% CI: 1.39–4.29; P=0.001), poor differentiated (HR: 1.72; 95% CI: 1.22–2.76; P=0.03) and undifferentiated tumours (HR: 2.37; 95% CI: 1.39–4.23; P=0.001) were associated with worse outcomes. CONCLUSIONS: The surgical margin status, clinical stage, and tumour differentiation were predictor variables for OS in this cohort of gastric cancer patients.